الإعجاز العلمي في القرآن (دراسة عن الإشارة العلمية في خلق الحشرات) - Artini Ariani; Wahyudin Wahyudin; Faisal Mubarak (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
Determining issue in this research is what is the scientific reference in the Qur’an about the creation of insects: especially about the creation of bees، of ants، and creation of spiders. This scientific research was used a library research. The researcher went beyond the objective interpretation approach. First، limiting the verses related to one topic، which is related to the creation of insects، then exposure to knowledge of occasions، then forming the topic as a whole in a proportional framework، supplementing the topic with the Hadith. Finally، the study of these verses is an objective and complementary study. The result of this research: First - the ability of bees to build hexagonal houses is the divine revelation، and that the Qur’an’s use of words was their significance for females، which is the indication that most of life’s work in the beehive is female، and that the different colors of honey are an effect of the different taste of bees And what I took out of it (honey) has many benefits. Secondly - in Surat An-Naml، verse 17-19، the facts of the scientific indication that the Qur’an’s use of words was indicative for females، which is an indication that female ants have a great role in the community of ants، and that the dialogue that took place between them in verse 18 of Surat al-Naml is an indication of the existence of means of communication As a language between them، and that the meaning of the words "your dwellings" indicates the regularity of the life of the ant community. Third - in Surat Al-Ankabut، verse 41، the facts of the scientific indication that the Qur’an’s use of words was denoting females، which is an indication that the female spider is the one who is responsible for making the fabric of the house، that the Almighty’s saying “the weakest of houses” refers to the phenomenon of family disintegration in the spider’s house. And all this wonderful limitation has been told by God in the holy Qur’an that people have recently known after the researchers revealed it. This is the scientific reference in the Qur’an.